Likuiditas, Solvabilitas dan Aktivitas Berpengaruh terhadap Profitabilitas pada Perusahaan Subsektor Perdagangan Eceran - Lioni Indrayani (Universitas Pamulang, 2020)
This study aims to examine the effect of Current Ratio (CR), Debt to Total Asset Ratio (DAR), (TATO) to Return On Asset (ROA) of retail trade sub-sector companies. The population in this research is financial statements from retail trade sub-sector companies listed on the Indonesia Stock Exchange period 2012-2018. While the sample of this research was determined by purposive sampling. This research uses E-Views to analyst data panel regression with Fixed Effect Model (FEM). The result of the research showed Current Ratio (CR) has no effect on Return on Asset (ROA), Debt to Total Asset Ratio(DAR) and Total Asset Turn Over (TATO) had a significant positive effect on Return on Asset(ROA).